2017
DOI: 10.1007/s11596-017-1732-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of microtubule-associated protein tau phosphorylation in Alzheimer’s disease

Abstract: As a major microtubule-associated protein, tau plays an important role in promoting microtubule assembly and stabilizing microtubules. In Alzheimer's disease (AD) and other tauopathies, the abnormally hyperphosphorylated tau proteins are aggregated into paired helical filaments and accumulated in the neurons with the form of neurofibrillary tangles. An imbalanced regulation in protein kinases and protein phosphatases is the direct cause of tau hyperphosphorylation. Among various kinases and phosphatases, glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 66 publications
3
35
0
1
Order By: Relevance
“…This indicates activation of inflammation in the hippocampus may induce excessive PTP1B production in mice displaying cognitive impairment. PTP1B can inhibit insulin signaling via the pIRS-pAKT-pGSK3β pathway [16,17] and induce Tau phosphorylation, disrupting synapse formation, and maintenance [64,65]. In the present study, we found that dietary MACs downregulated PTP1B expression, improved insulin signaling, and inhibited Tau over-phosphorylation in the hippocampus.…”
Section: Discussionsupporting
confidence: 60%
“…This indicates activation of inflammation in the hippocampus may induce excessive PTP1B production in mice displaying cognitive impairment. PTP1B can inhibit insulin signaling via the pIRS-pAKT-pGSK3β pathway [16,17] and induce Tau phosphorylation, disrupting synapse formation, and maintenance [64,65]. In the present study, we found that dietary MACs downregulated PTP1B expression, improved insulin signaling, and inhibited Tau over-phosphorylation in the hippocampus.…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, dietary β-glucan constrained microglia activation and reduced neuroinflammation in the hippocampus, suggesting enhancement of intestinal barrier function and reduction of LPS translocation might then be critical in β-glucan's beneficial effects on the inflammatory cascade in the hippocampus. Pro-inflammatory cytokines, such as TNFα, increase PTP1B transcription [10], block insulin signalling pIRS-pAKT-pGSK3β for synaptogenesis [11][12][13] and induce Tau phosphorylation, disrupting synapse formation and maintenance [36,37]. We found that chronic β-glucan supplementation down-regulated PTP1B, Synaptic ultrastructural plasticity is important for synaptic functional plasticity.…”
Section: Discussionmentioning
confidence: 71%
“…As one of the mechanisms to drive tau aggregation aberrant phosphorylation has been assumed, since hyperphosphorylation and aggregation of tau are both increased in AD [ 65 ]. Hyperphosphorylation of tau is most likely to result from an imbalance in the activities of specific tau kinases and phosphatases, causing an increased rate of tau phosphorylation and/ or decreased rate of de-phosphorylation [ 66 ]. Consequently, tau hyperphosphorylation reduces its binding affinity to microtubules, thereby induces a loss of tau’s normal microtubule-stabilizing function [ 67 , 68 ], and thus causes microtubule depolymerization [ 49 ].…”
Section: Tau Proteinmentioning
confidence: 99%